Manufacture of Requeijão cremoso processed cheese withgalactooligosaccharide - Belsito, P. C.; et. al. (2017)
tThe addition of galactooligosaccharide, (GOS, 0, 1.5, 3 or 4 g/100 g) on the quality parameters of requeijãocremoso was investigated. Chemical characteristics (pH, moisture, fat and protein), color (L*, a*, b*), watermobility by TD- nuclear magnetic resonance, rheology (flow curve and oscillatory tests), microstructureand sensory acceptance (consumer test) were evaluated. The addition of GOS provided a denser andcompact structure and reduced number and size of fat globules. Increased GOS level (3 and 4 g/100 g)improved the softness and spreadability (decrease of G , G and apparent viscosity and an increase of tan and melting index) and impacted positively on the aroma and taste of the requeijão cremoso. Overall,the addition of GOS in requeijão cremoso was proved to be a potential and interesting technologicaloption.